ANALISIS PENGARUH TOTAL ARUS KAS, KOMPONEN ARUS KAS, LABA AKUNTANSI. TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2016 - M Abdul Haris; Y Sunyoto (LPPM STIE DHARMAPUTRA SEMARANG, 2018)
ABSTRACTStock returns to be highly regarded by investors given the level of profit that will be enjoyed by investors of an investment that it does. Respondents of this study are manufacturing companies listed on the BEI in 2016. The number of samples of 67 companies taken based on the technique of Purposive Sampling. The data analysis to test the hypothesis using multiple regression is completed with SPSS program. From the result of this research, it can be concluded that: total cash flow, cash flow from investment activity and cash flow from funding activity does not have an effect on stock return, while cash flow from operating activity and accountancy profit have significant effect to stock return. Hypothesis 1 (H1) t value = 0.838 <t table = 1.66827 significant numbers = 0.206> 0.05 thus not significant. So H1 which states that there is influence between total cash flow to stock return rejected. Hypothesis 2 (H2) t value = 1.879> 1.66827 Significant number = 0,034 <0,05 thus significant. H2 thus states that there is an influence between cash flow from operating activities to stock return is accepted. Hypothesis 3 (H3) t value = 0.965 <1.66827 Significant number = 0.059 > 0.05 thus not significant. H3 which states that there is influence between cash flow from investment activity to return of stock declined. Hypothesis 4 (H4) t value = 1.472 <1.66827 signification number = 0.538> 0.05 thus not significant. H4 which states that there is influence between cash flow from funding activity to stock return is rejected. Hypothesis 5 (H5) t value = 1.669> 1.66827 Significant number = 0,000 <0.05 is thus significant. H5 which states that there is influence between accounting profit to stock return is accepted. Keywords: total cash flows, cash flows from operating activities, cash flows from investment activities, cash flows from liability activities, accounting earnings and returns